Assembling Lipid Membrane Scaffolds on Microgel-Based Artificial Cells through Vesicle Fusion onto the Hydrogel Network. - Allen,ME; Hindley,JW; Müller,MI; Cai,K; Kuimova,MK; Law,RV; Connell,SD; Wegner,SV; Ces,O; Elani,Y (ACS Nano, 2026)
Artificial cells assembled from materials such as hydrogels have emerged as platforms to replicate and understand biological functionalities, processes, and behaviors. However, hydrogels lack a lipid membrane, a vital property of cellular systems. Here we develop a process for the assembly of a fluid and stable lipid membrane which coats the hydrogel mesh network within the particle, through electostatically-mediated fusion of nanoscale lipid vesicles. This confers cell-mimetic and biotechnologically relevant properties upon microscale, cell sized, hydrogel artificial cells generated through microfluidics. We exploit the properties of the created membrane to augment existing hydrogel properties through permeability alteration and protection of the hydrogel from small molecule degraders. Furthermore, we show that the lipid membrane is compatible with organelle substructures within the hydrogels, which enables the exploitation of an enhanced material design space to build hydrogel artificial cells that increasingly mimic the organization of cells. This platform paves the way for producing next generation artificial cells and functional microdevices from interfaced hydrogel-lipid materials. Our technologies may underpin new opportunities for integrating membranes into hydrogel-based systems, inlcuding for drug delivery and tissue engineering.